Volumetric and optical properties of ACE inhibitor captopril in aqueous-alcoholic mixtures. Issue 5 (1st September 2017) - Deosarkar, Santosh D.; Pawar, Meenakshi P.; Arsule, Atmaram D.; Sawale, Rajendrakumar T.; Kalyankar, Tukaram M.
Abstract: Captopril is an angiotensin-converting enzyme (ACE) inhibitor that is used for the treatment of hypertension and congestive heart failure. This article addresses the accurate measurements of densities and refractive indices of solutions containing captopril in pure solvents such as water, methanol, ethanol and 1-propanol and aqueous mixtures of methanol, ethanol and propan-1-ol of 30%, 50% and 70% by volume in a wide range of drug concentration at 26 °C. This article also includes the evaluation of apparent molar volume, partial molar volume at infinite dilution and transfer volumes. The concentration dependence of the refractive indices studied and respective fitting parameters have been reported. Different properties are interpreted in terms of intermolecular interactions, effect of drug on structure of solvent/solvent mixture and overall structural fittings in solutions.